Effects of immunosuppressive and biological agents on refractory Takayasu arteritis patients unresponsive to glucocorticoid treatment. Issue 5 (May 2017) - Ohigashi, Hirokazu; Tamura, Natsuko; Ebana, Yusuke; Harigai, Masayoshi; Maejima, Yasuhiro; Ashikaga, Takashi; Isobe, Mitsuaki
Abstract: Background: We aimed to investigate the effects of immunosuppressive and biological agents on refractory Takayasu arteritis (TA) patients resistant to or dependent on glucocorticoids. Methods: Forty-four consecutive TA patients were enrolled, and the clinical characteristics and effectiveness of the immunosuppressive and biological agents in achieving and maintaining remission among glucocorticoid-resistant or glucocorticoid-dependent patients were investigated. Results: Fifteen patients showed favorable response to the initial glucocorticoid treatment, and 29 patients exhibited resistance to initial glucocorticoid treatment or relapsed with tapering glucocorticoid. Of the 29 patients, 5 responded to additional glucocorticoid treatment, and 22 of the remaining 24 glucocorticoid-resistant or glucocorticoid-dependent patients were prescribed immunosuppressive agents. Methotrexate was the most commonly used in these patients as the first-line treatment. In total, 10 patients maintained remission using immunosuppressive agents, with the effectiveness of each agent about 20%. The only significant difference between patients who were and were not able to achieve and maintain remission with immunosuppressive agents was the presence of the HLA-B52 allele ( p  < 0.0001). Biological agents were administered to 6 patients refractory to immunosuppressive agents. All patients were administered tumor necrosis factor (TNF) inhibitors as the first-line treatment, and 3 patients maintained remission. Anti-interleukin-6 receptor antibody was administered to 2 patients who were resistant to the TNF inhibitors, and 1 patient achieved and maintained remission. Conclusion: In our cohort, 64% of the glucocorticoid-resistant or glucocorticoid-dependent patients maintained remission through a combined treatment with glucocorticoid, immunosuppressive agents, and/or biological agents. The combined use of immunosuppressive and biological agents appears to be a promising treatment option for achieving and maintaining remission in refractory TA patients.